2020
DOI: 10.1177/0040517520904374
|View full text |Cite
|
Sign up to set email alerts
|

The effects of textile reinforcements on the protective properties of self-healing polymers intended for safety gloves

Abstract: In the environment where glove material is exposed to harmful chemicals, hazards related to faster penetration of dangerous substances into the glove interior may cause microdamage. One of the solutions to overcome this problem is to use the self-healing polymeric materials that can minimize economic loss and accidents in the workplace. The current work aims to present the impact of different types of textile reinforcement on the effectiveness and efficiency of the self-healing process of methyl vinyl silicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This is the case with research focused on the manufacturing of worker gloves with high protective performance. The main healing composite is composed of methylvinyl silicone rubber containing hybrid molecules with an inorganic silsesquioxane, and the base fabric is made of cotton or polyamide fibers [85]. The results of several tests conclude that the textile shows great resistance to conditions such as penetration, abrasion, and puncture, which makes it very suitable to wear when working with hazardous chemicals.…”
Section: Workwearmentioning
confidence: 99%
“…This is the case with research focused on the manufacturing of worker gloves with high protective performance. The main healing composite is composed of methylvinyl silicone rubber containing hybrid molecules with an inorganic silsesquioxane, and the base fabric is made of cotton or polyamide fibers [85]. The results of several tests conclude that the textile shows great resistance to conditions such as penetration, abrasion, and puncture, which makes it very suitable to wear when working with hazardous chemicals.…”
Section: Workwearmentioning
confidence: 99%
“…To understand the effect of textile reinforcement, three unwoven fabrics of different raw materials and the same structure (polyamide, cotton-polyamide, and cotton) were taken, and it was found that the fabric treated with textile reinforcement shows higher stability. It has also been tested that the composites of methyl vinyl silicon rubber and silsesquioxanes can be upgraded with the addition of textile reinforcement, and these types of composites provide good chemical permeation resis-tance that makes this material suitable for use in barrier protection [69]. For the preparation of a self-healing electromagnetic interference shielding fabric, carbon nanotubepoly(2-hydroxyethyl methacrylate) is aligned on a nonwoven fabric with magnetic field electrospinning and cross-stacking fabric layers that are aligned as shown in Figure 8.…”
Section: Textilementioning
confidence: 99%
“…Indeed, these gloves must protect the consumers to a well-defined level and at the same time ensure easy and rapid perspiration of the hands when wearing. Based on the Irzma nska et al' studies [11][12][13], protective gloves can be one of the solutions to overcome the use of the self-healing polymeric materials that can minimize economic loss and accidents in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that impregnating coating fluids (STF) composed of hard, silica particles into woven, nonwoven and composite fabrics provide protection for users was effectively improved by coating with 20 wt.% SiC particles exhibiting the best stab resistance against knife cut [18][19][20]. However, proposed examples of colloidal solutions based on suspension of silica have been applied to fabrics as shear thickening fluids [4,11,21]. Indeed, they are made by suspension of nanoparticles in polymer or submicron silica particles into fabrics [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation